Abstract 17220: Mathematical Modeling of Echocardiographic Underestimation of Right Ventricular Systolic Pressure in Severe Tricuspid Regurgitation - Smith, Tyler J; Appadurai, Vinesh; Gercek, Muhammed; Maganti, Kameswari; Lee, Jeesoo; Markl, Michael; Thomas, James D (Circulation (New York, N.Y.), 2023)
Background: Echocardiography approximates right ventricular systolic pressure (RVSP) by the simplified Bernoulli Equation (SBE), adding mean right atrial pressure (mRA) to convective pressure (4v2), where v is maximal tricuspid regurgitant (TR) velocity. As TR worsens, the inertance of TR flow increases which may cause TR peak velocity to lag behind the maximal RVSP time point. As a result, using SBE may underestimate RVSP in patients with significant TR. Currently, inertance is not measurable by echo, but theory suggests it is linearly related to regurgitant orifice diameter (3 X ROD). We sought to confirm the principle of RVSP underestimation in ≥severe TR by comparing a lumped parameter model (LPM) of the heart to cath/echo data. Methods: In MATLAB, the LPM uses time-varying elastance of atria/ventricles and the complete Bernoulli equation to model pressure and flow in all chambers/vascular beds. LPM parameters for trace and torrential TR cases yielded convective, inertial, RA and RV pressure curves and critical TR variables: TR volume, mRA, and TR velocity, which were compared to simultaneous cath/echo data in clinical patients. Results: Trace TR pressure curves aligned with RVSP and convective pressure peaks, and near perfect echo prediction. Torrential TR pressure curves show earlier peak RVSP with up to 20mmHg of inertial pressure, resulting in predicted 3.1mmHg underestimation, closely matching the observed underestimation of 3.6mmHg. For modeling demonstration, we show (from 90 subjects) 1 patient with trace TR (ROD 1.1mm), A, and 1 patient with torrential TR (ROD=11.3mm), B, in Figure 1. Conclusions: Our analysis shows the importance of inertial pressure in ≥severe TR: earlier peak RVSP congruent with accelerating increased regurgitant mass and improved approximation of RVSP by inertial pressure quantification modeling. Further clinical study of RVSP underestimation in cases of ≥severe TR and its correction by including inertial forces is recommended.